Manufacture by Selective Laser Melting & Physical Behaviour of Commercial 316L Stainless Steel - Nurul Kamariah, Md Saiful Islam; Wan Sharuzi, Wan Harun; S. A., Che Ghani; Z., Ghazalli; Dayangku Noorfazidah, Awang Sh'ri; Mohd Azrul Hisham, Mohd Adib; Idris, Mat Sahat (International Medical Device and Technology Conference 2017, 2017)
Selective Laser Melting is one of the technologies used to fabricate 3D sample directly through high energy focused laser. This method has a high potential in fabricating biocompatible material 316L stainless steel for biomedical implant devices. The final properties of the product fabricated by SLM is controlled by initial processing parameters. This paper aims to study the effect of building orientation during the fabrication process of SLM on the dimensional accuracy of the fabricated 316L stainless steel. The dimensional accuracy was measured and analysed for three different as-built sample conditions fabricated through SLM process at three different build orientation which are at 0 degree, 45 degree and 90 degree building orientations. It is found that 0 degree building orientation exhibits the lowest dimensional accuracy compare to others which are contributed by the deformation that occurs during sample fabrication.